An Experimental Study on the Effects of Discovery Learning and Differentiated Instruction on Cognitive and Affective Aspects in Mathematics Education - Asriko Muhsi (JMEA : Journal of Mathematics Education and Application, 2025)
This experimental study investigates the effects of Discovery Learning and Differentiated Instruction on students’ cognitive and affective learning outcomes in mathematics education. Specifically, it examines the impact of these instructional models on problem-solving ability and interest in learning mathematics among eleventh-grade students. The research employed a quasi-experimental design with a pretest-posttest control group, involving 60 students divided equally into three groups: a control group (conventional instruction), an experimental group with Discovery Learning, and another with Differentiated Instruction.Data were collected using a validated problem-solving test and a mathematics interest questionnaire. The results revealed that both experimental groups significantly outperformed the control group in posttest scores. The Discovery Learning group achieved the highest mean scores in both cognitive (M = 85, SD = 5) and affective (M = 88, SD = 4) domains, followed closely by the Differentiated Instruction group (M = 82, SD = 6 for problem-solving; M = 85, SD = 5 for interest). One-way ANOVA showed significant differences among the groups (F = 36.92, p 0.001), and Tukey HSD tests confirmed that both experimental groups differed significantly from the control group, though not from each other.These findings suggest that both Discovery Learning and Differentiated Instruction are effective in improving students’ mathematical reasoning and motivation. Their student-centered nature and alignment with constructivist principles make them suitable strategies for enhancing mathematics instruction, particularly in diverse classrooms. Educators are encouraged to adopt either model to improve student outcomes both cognitively and affectively